Taking the measure of work : a guide to validated scales for organizational research and diagnosis - Fields, Dail L. (Emerald Publishing Limited, 2013)
This book is a handbook for people who want to assure the use of reliable and valid questionnaires for collecting information about organizations. It significantly reduces the time and effort required for obtaining validated multi-question measures of aspects of organizational 'health' such as employee job satisfaction, organizational commitment, organizational justice, and workplace behaviors. It helps users in measuring some factors underlying employee perceptions of work such as job characteristics, role ambiguity or conflict, job stress, and the extent to which employees believe their values and those of the organization are congruent. All the measures in the book have been used and tested in research studies published in the 1990's. In addition, all the measures describe the extent and types of reliability and validity tests that have been completed, a feature that organizational researchers should find particularly useful. All in all, this book is a handy tool to increase the efficiency of researchers, consultants, managers, or organizational development specialists in obtaining reliable and valid information about how employees view their jobs and organizations.